Implementasi metode fuzzy logic pada rancang bangun bak sampah buka tutup otomatis berbasis raspberry pi pico - oktavia safitri; Titi Andriani; Paris Ali Topan; Indra Darmawan (Program Studi Teknik Elektro, 2023)
Cleanliness is an important factor in everyday life, therefore cleanliness must be maintained to avoid disease and environmental pollution. Actually, there have been prevention efforts to prevent problems regarding waste, starting from providing open trash bins if not cleaned it will cause odors as well as closed garbage bins are still not effective because people who want to dispose of garbage have to open the lid manually, especially if the trash bin is dirty people will reluctant to take out the trash. Therefore, a modified trash bin was created to produce a smart trash can to attract people who want to dispose of garbage. This tool uses a Raspberry pi pico as a controller, a PIR sensor as a detector of the presence of objects around the trash can, a servo motor to move the lid of the trash can, a buzzer as an indicator to determine the condition of the trash can and a fuzzy method to make the right decision for the distance to be determined by the user. ultrasonic to make the buzzer turn on.